2011
DOI: 10.1002/bit.23232
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of neuronal precursors differentiation induced by substrate nanotopography

Abstract: Embryonic stem (ES) cell differentiation in specific cell lineages is a major issue in cell biology particularly in regenerative medicine. Differentiation is usually achieved by using biochemical factors and it is not clear whether mechanical properties of the substrate over which cells are grown can affect proliferation and differentiation. Therefore, we produced patterns in polydimethylsiloxane (PDMS) consisting of groove and pillar arrays of sub-micrometric lateral resolution as substrates for cell cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 46 publications
(56 reference statements)
0
57
0
Order By: Relevance
“…The dimension (depth) and stiffness were found to highly co-regulate the spreading of human umbilical vein endothelial cells on round pillars of silica or PDMS [60] or the spreading of bovine aortic endothelial cells on grooves of PA [53], whereas our data indicated that topography is more predominant than stiffness and dimension (width) in rBMSC spreading (area). Another example is that the rat Schwann cell precursor line is most likely aligned in the narrowest and deepest grooves and differentiate toward early Schwann cells on stiffer, narrower grooves [44], whereas the main body of evidence [5,46,47,51,61,62], including ours here, support that MSCs are in favor of a soft substrate to differentiate into neuronal cells. Thus, caution should be taken when the predominance of regulating factors is applied into other types and/or dimensions of topographical substrates because the importance of each regulating factor depends on the cell types, material properties, as well as mechanotransductive signaling, which will be investigated in future studies.…”
Section: Discussionmentioning
confidence: 83%
“…The dimension (depth) and stiffness were found to highly co-regulate the spreading of human umbilical vein endothelial cells on round pillars of silica or PDMS [60] or the spreading of bovine aortic endothelial cells on grooves of PA [53], whereas our data indicated that topography is more predominant than stiffness and dimension (width) in rBMSC spreading (area). Another example is that the rat Schwann cell precursor line is most likely aligned in the narrowest and deepest grooves and differentiate toward early Schwann cells on stiffer, narrower grooves [44], whereas the main body of evidence [5,46,47,51,61,62], including ours here, support that MSCs are in favor of a soft substrate to differentiate into neuronal cells. Thus, caution should be taken when the predominance of regulating factors is applied into other types and/or dimensions of topographical substrates because the importance of each regulating factor depends on the cell types, material properties, as well as mechanotransductive signaling, which will be investigated in future studies.…”
Section: Discussionmentioning
confidence: 83%
“…Several studies have provided insights into mechanisms promoting accelerated neural differentiation and tissue regeneration (33,34). In complimentary clinical and experimental studies, documented imbalances of neuromediators found in denervated tissue are associated with conditions where delayed wound healing is common.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 For instance, cultured neurons have been tested on different nanosurfaces by several investigators. 3,4 Structured materials which facilitate dendrite development, adhesion, and signaling may promote better understanding of neuronal repair from pathological conditions and present novel therapeutic strategies. 5,6 Another example of the ramified cell is the glomerular podocyte.…”
Section: Introductionmentioning
confidence: 99%